Rodinný dům s květinářstvím - Pobucká, Slávka (Vysoké učení technické v Brně. Fakulta stavební)
Předmětem bakalářské práce je návrh novostavby rodinného domu s květinářstvím. Stavba je umístěna v obci Hutisko – Solanec, okres Vsetín. Objekt je samostatně stojící, dvoupodlažní a částečně podsklepený. Dům je určený pro trvalé bydlení čtyřčlenné rodiny. Půdorys domu je nepravidelného tvaru, který vychází z tvaru pozemku. Zastřešení stavby je řešeno sedlovou střechou. Objekt je založen na základových pasech z prostého betonu. Svislé nosné konstrukce jsou navrženy z keramických tvárnic Heluz a betonových tvárnic ztraceného bednění. Nosná konstrukce střechy je tvořena vaznicovým krovem a prefabrikovanými dřevěnými vazníky. Dům je rozdělen na obytnou část a květinářství.

The aim of this bachelor thesis is a design of new building detached house with florist. Construction is situated in the village of Hutisko – Solanec in the Vsetín district. The building is a detached house, it has two floor and a partial basement. The detached house is designed for permanent housing for a four member family The floor plan of the building is of an irregular shape, based on the shape of the land parcel. The house roofing is designed with a gable roof. The construction is based on plain concrete strip foundations. The vertical load-bearing structures are designed to be bulit of clay blocks Heluz and concrete blocks of permanent formwork. The load-bearing roof assembly is built of timber roof truss and prefabricated timber truss girders. The building is divided into a living area and florist.
Detached house with florist
Keywords: rodinný dům; květinářství; dvoupodlažní; částečně podsklepený; krov; sedlová střecha; detached house; florist; two floor; partial basement; roof truss; gable roof